Penerapan Strategi Flipped Classroom dengan Pendekatan Scientific dalam Pembelajaran Matematika pada Kelas XI SMKN 2 Padang Panjang - Usmadi Usmadi; Ergusni Ergusni (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
The issues in this study are how learning outcomes, learning motivation and student’s interest in mathematics learning material are being affected after applying classroom flipped learning strategies with a scientific approach to class XI grade students of SMK 2 Padangpanjang? Are student’s learning outcomes by applying classroom flipped strategies with the scientific approach are better than the one that does not apply that method? This study aims to describe student’s learning outcomes, motivation, and interests in mathematics learning, and to see whether the experimental class learning outcomes are better than the control class. This research was conducted at SMK 2 Padang Panjang in the academic year 2017/2018. The sample is taken by using the random sampling technique which consisted of two sample groups, and each is consisted of 28 people. Based on the results of the study, it can be concluded that the student’s mathematics learning outcomes are better than the previous one. In addition, student’s motivation towards mathematics learning is in a high level and students' interests as well.